As possíveis significações da palavra discurso em propostas de trabalhos acadêmicos - Furquim, Ana Júlia Queiroz (2009)
This dissertation aims at verifying possible meaning of the word discourse in academic abstracts in the area of Linguistics. It was taken as corpus abstracts from SILLEL Letters and Linguistics Simposium at Federal Universiy in Uberlândia. Research focus was centered in different theoritical conceptions of the word discourse according its use by research s episthemological inscriptions. The research hypothesis is that there is our equivocity relation which provoks delocations in the suveral meanings the word discourse can be taken in academic abstracts. French Discourse Analysis was considered as theoretical framework, mainly notions of discourse and subject by Michel Pêcheux (1975/1990,1975/1997, 1983/2002). Mikhail Bakhtin s approach of enunciation, dialogy and polyphony were mentioned as referential support. As methodological tools it was emphasized Santos (2004) notion of Semic Essence which composed a meaning conjuncture to analyse conceptual contrasts on the word discourse. It was also considered as a complementar theoretical basis, notions on theoretical framework of Textual Linguistics. Analysis shower epistemological equivocates, both in on internals or exterior theoretical amplitude.